COMPOSITE RADAR ABSORBING MATERIAL CHARACTERISTIC MEASUREMENT USING FREE SPACE METHOD - RAMA, ALDRIN
Composite radar absorbing material has been widely used in airplane, especially in military fighter for stealth. Aside from its great mechanical properties, composite material also has great electromagnetic characteristics to absorb radar. This topic is done to start the research regarding radar absorbing material in Faculty of Mechanical and Aerospace ITB. Measurement was done by creating a plate of Glass Fiber Reinforced Polymer (GFRP) varied by width and fiber orientation then tested it using free space measurement method at frequency range of 8-12 GHz to get it radar absorption characteristic in term of S parameters. The radar absorption gets better with the addition of the material thickness. GFRP with total plies of 16 has 4% better absorption compared to GFRP with plies of 4. Different measurement method results in different S parameter. On the other hand, numerical simulation to model the free space measurement was also done by using Altair FEKO to get the radar absorption characteristic of the material in term of S parameters. The result shows different value and pattern compared to the measurement model of rectangular waveguide from related research from another journal. However, the numerical simulation result shows the similar pattern compared to the free space experiment.